Outcomes of Telemedicine Intervention in a Regional Intensive Care Unit: A before and after Study. Issue 5 (September 2017) - Panlaqui, O. M.; Broadfield, E.; Champion, R.; Edington, J. P.; Kennedy, S.
Telemedicine consultations in remote intensive care units (ICUs) overseas were found to be effective in reducing mortality and hospital length of stay (LOS). In Australia, there were anecdotal reports of these clinical outcomes. This retrospective before and after study assessed the improvement in patient outcomes with the implementation of a telemedicine program in a regional high dependency unit. Daily virtual consultations were conducted between the rural facility and the intensivists at the regional centre. A total of 525 patients received intensive care support between 2010 and 2015. Hospital and High Dependency Unit mortality showed no evidence of significant differences between the telemedicine group and the baseline (relative risk 1.02, 95% confidence interval [CI] 0.99–1.06, P=0.25 and relative risk 1.00, 95% CI 0.98–1.03, P=0.67 respectively). The hospital LOS was lower in the baseline group by 1.5 days. There was no significant difference in High Dependency Unit LOS. To adjust for the covariates in LOS, log linear regression analysis was performed. The telemedicine intervention, Acute Physiology and Chronic Health Evaluation II scores and inter-hospital transfers were found to contribute significantly to hospital LOS. The most important result of the study was that the proportion of inter-hospital transfers was lower in the telemedicine group (relative risk 0.88, 95% CI 0.80–0.98, P=0.03) compared to baseline. This means that critically ill patients in our regional centre can continue to receive specialist care remotely through tele-ICU consultations thus avoiding the need for patient transport. However, further study is needed to establish the benefits and risks of telemedicine intervention in ICUs in Australia.